Steganography Test for Exif Metadata on JPEG Files With AES-256 Encryption for Secret Message Security - Yasir Hasan (Sean Institute, 2025)
One of the main challenges is hiding secret messages in media such as JPEG images. However, embedding messages directly into EXIF metadata can pose detection risks and vulnerability to forensic analysis attacks, and this technique faces challenges in security, resistance to metadata manipulation, and message extraction accuracy. The method used in this study involves embedding a message encrypted using AES-256 ECB mode and Base64 into the EXIF metadata of JPEG files, so that only those with the decryption key can access the message content. This system is designed to be compatible with standard image processing software without changing the main structure of the JPEG file, making it difficult to detect by conventional metadata analysis techniques. Test results show that this method is able to embed secret messages with a high level of security without changing the visual quality of the image. AES-256 encryption encoded in Base64 is proven to be effective in maintaining the confidentiality of messages, so that only users with the correct decryption key can access them. Thus, the combination of EXIF metadata steganography and AES-256 encryption in Base64 provides an effective solution for securing secret messages in JPEG files, improving data protection against the threat of information theft and manipulation.